Strategi Social Media Marketing Instagram RFAS Music dalam Peluncuran Lagu “Berona” Karya Rizky Febian - Fadhilah Medy Putra Ramadhan; Agus Hermanto (Dialogika : Jurnal Penelitian Komunikasi dan Sosialisasi, 2026)
Social media provides significant benefits in life, one of which is as a communication and promotional tool. Instagram, as the platform with the second most users in the world, is a strategic medium for promotion. This study analyzes RFAS Music's strategy in utilizing Instagram to promote the song "Berona" by Rizky Febian. This study uses a descriptive qualitative approach with structured interviews, observation, and documentation methods. The collected data are analyzed through the process of data reduction, data presentation, and drawing conclusions. The theories used are the Technology Acceptance Model (TAM) which emphasizes technology acceptance and Quesenberry's Theory which emphasizes marketing communications. The results of the study indicate that RFAS Music successfully implemented an Instagram social media marketing strategy to create interaction and attract the attention of the target audience. This strategy not only increases audience awareness of the new song but also strengthens RFAS Music's position in the music industry. Thus, this study can be concluded that RFAS Music's strategy is a social media promotion strategy that pays attention to the level of efficiency and the times. By implementing the strategy and linking it to marketing communications, RFAS Music successfully promoted the launch of Rizky Febian's song "Berona." The study suggests that it would be better if this promotional activity also used other platforms that are currently equivalent and as widely used as Instagram. and continue to improve interesting strategies.customers